Strong user rights in fisheries: Delineating the impacts - Ragnar Arnason; Birgir Runolfsson (University of Iceland, Institute of Economic Studies (IoES), 2022)
User rights in fisheries refer to the rights of fishers to harvest from fish resources. In terms of security, exclusivity, duration, and transferability these rights can be strong or weak. In recent years there has been a substantial movement toward stronger user rights in many fisheries around the globe and further shifts of the same kind are recommended by many fisheries advisors. The transition from weak to strong user rights in fisheries has a wide range of impact. Here we attempt to identify and describe some of the more prominent of these impacts. It is convenient to divide these impacts into economic, environmental, and social impacts. Though this classification is by no means perfect or even exhaustive, it can serve as a framework for further research in the field. We then provide some discussion of the social desirability and undesirability of the various impacts. This discussion, however, is in broad terms and very preliminary.
Keywords: B10; B25; P14; P48; Q22; Q28; 330; User rights in fisheries; property rights in fisheries; property rights; strong userrights; impacts of strong user rights; SURFs